TAXATION OF PROFITS FROM OPERATIONS WITH “VIRTUAL ASSETS” – LEGAL ANALYSIS OF THE DRAFT LAW ON CHANGES IN THE TAX CODE OF UKRAINE - Hrytsai, Serhii (Scientific Journal of Polonia University, 2023)
The article provides a legal analysis of the Draft Law No. 7150 dated 13.03.2022 on Amendments to the Tax Code of Ukraine related to the adoption of the Law of Ukraine “On Virtual Assets” No. 2074-IX dated 17.02.2022. It is aimed at developing mechanisms for taxation of profits from transactions with “virtual assets”, which are more commonly known as cryptocurrencies. From the point of view of tax legislation regulation of these phenomena, a public law entity is certainly tempted to introduce a new payment and/or a special tax regime into the tax legislation. This, of course, would be quite beneficial from the point of view of the efficiency of realization of budgetary obligations of any country, but the occurrence of such a situation may increase the tax burden. This will be an objective reason for the logical migration of “virtual” business, which is very mobile, to other countries with a more attractive tax regime. The purpose of this article is to define the tax concept chosen by Ukraine as laid down in the legal provisions of Draft Law No. 7150. The results of the study indicate that Ukraine has chosen a conservative approach to the choice of the taxation system for virtual assets. It is envisaged to apply the existing types of taxes and provisions of the Tax Code of Ukraine to the taxation of the circulation of virtual assets, i.e. without introducing special taxes exclusively for the taxation of virtual assets. This is a global trend in the formation of tax policy towards cryptocurrencies.